Koinfeksi bakteri pada pasien COVID – 19 di ICU - Wani Devita Gunardi; Grace Raveena Widelia; Donna Mesina Pasaribu (Jurnal MedScientiae, 2022)
In previous influenza pandemics, bacterial coinfection was the most common cause of death. In the COVID-19 pandemic, bacterial coinfection also led to high mortality rates in COVID-19 patients in the ICU. This study was conducted to determine the bacteria that cause coinfection in COVID-19 patients in the ICU. A search was conducted on the Pubmed database and 7 journals were selected for review. From the results of the analysis of these journals, the most bacterial identified that cuased co-infection in COVID-19 patients in the ICU were Stenotrophomonas maltophilia (33.8%), followed by Acinetobacter baumannii (22.65%), Pseudomonas aeruginosa (22.44%) and Staphylococcus aureus (16.77%). The discovery of these bacteria was related to the length of stay in the ICU, the use of a mechanical ventilator and the administration of antibiotics before entering the ICU.